Analysis of acrylamide in food products by microchip electrophoresis with on-line multiple-preconcentration techniques. (15th October 2016) - Wu, Minglei; Chen, Wujuan; Wang, Guan; He, Pingang; Wang, Qingjiang
Highlights: The MCE method was first used for acrylamide determination in food samples. The multiple-concentration strategy afforded 432-fold improvement in detection sensitivity. The detection limit of acrylamide was 1 ng/mL. This method was successfully applied to acrylamide analysis in potato chips and French fries. Abstract: In this paper, a microchip electrophoresis method based on on-line multiple-preconcentration techniques combining field-amplified sample stacking and reversed-field stacking was developed for highly efficient analysis of acrylamide in food products. The related mechanism as well as important parameters governing separation and preconcentration have been investigated in order to obtain maximum resolution and sensitivity. The best separation was achieved using a 100 mM borate solution at pH 9.3 as running buffer, and a sensitivity enhancement factor of 432 was obtained using this concentration method under optimal conditions. The detection limit of acrylamide was 1 ng/mL, which was comparable to those previously obtained using CE methods with on-line preconcentration techniques and was 41–700 times lower than those previously reported CE methods without concentration process. The proposed method also gave satisfactory and reliable results in the analysis of acrylamide in potato chips and French fries.